Meyeroguilline E, a New Isoindolinone Alkaloid from the Poisonous Mushroom Chlorophyllum molybdites, and Identification of Compounds with Multidrug Resistance (MDR) Reversal Activities - Lee, Bum Soo; Ryoo, Rhim; Park, Jin Song; Choi, Sang Un; Jeong, Se Yun; Ko, Yoon-Joo; Kim, Jung Kyu; Kim, Jin-Chul; Kim, Ki Hyun (ACS Publications, 2022)
Three isoindolinone alkaloids (1-3), including one new isoindolinone-type alkaloid, meyeroguilline E (1), and six other known compounds (4-9) were isolated from the poisonous mushroom Chlorophyllum molybdites (Agaricaceae). The structure of the new compound was determined using extensive spectroscopic analyses via one-dimensional (1D) and two-dimensional (2D) NMR data interpretation and high-resolution electrospray ionization mass spectrometry (HR-ESI-MS). To the best of our knowledge, compound 1 is the first example of a natural isoindolinone with a butanoic acid moiety, and this study is the first to detect the other known compounds (2-9) in C. molybdites. The isolated compounds (1-9) were examined for their multidrug resistance (MDR) reversal activity against MES-SA, MES-SA/DX5, HCT15, and HCT15/CL02 human cancer cells. Based on the results, 20 mu M of compounds 3 and 6 slightly potentiated paclitaxel (TAX)-induced cytotoxicity in MES-SA/ DX5, HCT15, and HCT15/CL02 cells; however, the compounds had no effect on the cytotoxicity against MES-SA and nonMDR cells.